On adding IEC61131-3 support to ROS based robots - Mário Jorge Rodrigues De Sousa (2013)
ROS (Robot Operating System) is a framework for the development of robotic applications widely used throughout research community due to its modular architecture and distributed nature. Using this framework a robot application consists of several nodes that exchange data over a common middle-ware. Programming new nodes is done by using a ROS API (application programming interface) on one of the available programming languages, such as C++ and python. It is our intention to build a robot that needs to be partially programmed in IEC 61131-3, allowing the end-user to adapt it to any specific industrial environment. In this work we have specified a mapping between the concepts defined in IEC 61131-3 and ROS, and started implementing a library through which IEC 61131-3 programs may co-ordinate their actions with the remaining ROS based robotic application.